Evaluation the results of the treatment of displaced intra-articular distal radius fractures in adults by Kirchner wires - سعد, معن (Latakia University Journal -Medical Sciences Series, 2024)
Objective of the study: to evaluate the functional and healing results of displaced intra articular distal radius fractures in adults by studying the advantages and disadvantages of surgical treatment using Kirchner wires "K-wires". Materials and methods : this study included 34 patients from the reviewers of Tishreen University Hospital in Lattakia between 2021-2022. All patients in the study underwent fixation of the displaced intra articular distal radius fractures using K-wires after appropriate clinical and Radiological evaluation . Rehabilitation was recommended for all patients after surgery and patients were followed up at maximum intervals 12 months of treatment. Results: the study sample consisted of 34 patients with a predominance of females by more than 64%. The majority of patients participating in the study were in the age group between 51-65 years, in half of the cases .The majority of cases were right-sided injury, with no bilateral cases were recorded . With the control of fractures of type c1, while no case of type c3 was recorded in the research sample. When studying the range of wrist movement and estimating the mean values, little determination was found in patients with K-wires , and the same applies to grip strength due to delays in physical therapy and the length of stay of the splint . A small percentage of the occurrence of the following disorders was observed: infection, secondary mutation, and Sudeck dystrophy , while no cases of non-healing were recorded in the study sample . Conclusion: this study showed the positive results of the treatment of fractures of the displaced intra articular distal radius fractures using K-wires , and the importance of this surgical technique in the management of these cases.